2016
DOI: 10.1182/blood-2015-10-675629
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function variant in DIAPH1 causes dominant macrothrombocytopenia and hearing loss

Abstract: Key Points• A gain-of-function variant in DIAPH1 causes macrothrombocytopenia and hearing loss and extends the spectrum of DIAPH1-related disease.• Our findings of altered megakaryopoiesis and platelet cytoskeletal regulation highlight a critical role for DIAPH1 in platelet formation.Macrothrombocytopenia (MTP) is a heterogeneous group of disorders characterized by enlarged and reduced numbers of circulating platelets, sometimes resulting in abnormal bleeding. In most MTP, this phenotype arises because of alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(168 citation statements)
references
References 46 publications
8
158
1
1
Order By: Relevance
“…It has been shown that specific GOF variants in DIAPH1 and SRC can cause a defect in megakaryopoiesis, whereas this is not expected of LOF variants. 22,48 Similar observations can be made for SFLN14, where all variants are located in the ATPase-AAA-4 domain, and rare variants outside this domain seem not to result in an IPD. 54 There are publicly accessible databases such as ClinVar, 94 DECIPHER, 95 and Exome variant server 96 and access-for-a-fee databases such as the Human Gene Mutation Database (HGMD) 97 that record disease-associated variants.…”
Section: Assigning Pathogenicity To Novel Variants: Use Of Public Datsupporting
confidence: 59%
See 3 more Smart Citations
“…It has been shown that specific GOF variants in DIAPH1 and SRC can cause a defect in megakaryopoiesis, whereas this is not expected of LOF variants. 22,48 Similar observations can be made for SFLN14, where all variants are located in the ATPase-AAA-4 domain, and rare variants outside this domain seem not to result in an IPD. 54 There are publicly accessible databases such as ClinVar, 94 DECIPHER, 95 and Exome variant server 96 and access-for-a-fee databases such as the Human Gene Mutation Database (HGMD) 97 that record disease-associated variants.…”
Section: Assigning Pathogenicity To Novel Variants: Use Of Public Datsupporting
confidence: 59%
“…This collaborative approach will provide the platform to evaluate existing and new interventions to gather evidence for the best approach to treatment. That such international approaches can be successful has been demonstrated by the BRIDGE-BPD and ThromboGenomics consortium efforts reported in this issue 22,82 and in other journals.…”
Section: Human Phenotype Ontologymentioning
confidence: 93%
See 2 more Smart Citations
“…WES, and particularly WGS, offer the potential to identify new genes, especially when combined with selective approaches such as comparing patient phenotypes with those of knock-out mouse models or gene datasets; approaches that allowed us to identify TRPM7 (from an existing mouse model) and DIAPH1 (from a search of genes responsible for deafness) in patients belonging to the French cohort which we submitted to BRIDGE. 10,11 Recent advances in bioinformatic analysis of next-generation sequencing data are enhancing causal gene identification in IPDs, helped by HPO questioning and the study of variant penetrance within large families. 12 It would be interesting to now apply WGS to those cases in the Spanish cohort for whom disease-causing variants were not identified.…”
mentioning
confidence: 99%